Spawning Potential Ratio Can Provide Reference Points for Fishery Management That Are Robust to Environmental Variability - Kyle W. Shertzer; Matthew D. Damiano; Erik H. Williams (Fishes)
Biological reference points are key quantities provided by stock assessments and used in fishery management for evaluating fishery status and setting future catch levels. For many fisheries worldwide, biological reference points are based on the spawning potential ratio (SPR), which measures per-recruit reproductive output as a function of the fishing rate relative to that when fishing is absent. SPR depends on the biological characteristics of the stock, which in turn can be influenced by the environment. A fishing rate based on SPR is often used as a proxy for the fishing rate that provides maximum sustainable yield. Here, we evaluate variability in the fishing rate (F40) that provides an SPR of 40%, a commonly used limit reference point, given plausible variability in biological characteristics. Using eight case-study species from marine waters off the southeast United States, we consider both simple random variability and directional variability, both of which might result from climate change. We test the sensitivity of F40 to various life-history traits and compute distributions of F40, given the expected variability in those traits. Based on those distributions, we evaluate the probabilities of overfishing given a target fishing rate (here, 75%F40) that is based on prevailing conditions without considering future variability in F40, consistent with common, current practice. Analyses also considered an SPR of 30% and 50% to evaluate the generality of conclusions. Results support that SPR-reference points are generally robust to plausible levels of variability in life-history traits that might be induced by environmental nonstationarity and that associated target fishing rates can provide meaningful buffers to prevent overfishing.